If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 8 = x + 5 Reorder the terms: 8 + 5x = x + 5 Reorder the terms: 8 + 5x = 5 + x Solving 8 + 5x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 5x + -1x = 5 + x + -1x Combine like terms: 5x + -1x = 4x 8 + 4x = 5 + x + -1x Combine like terms: x + -1x = 0 8 + 4x = 5 + 0 8 + 4x = 5 Add '-8' to each side of the equation. 8 + -8 + 4x = 5 + -8 Combine like terms: 8 + -8 = 0 0 + 4x = 5 + -8 4x = 5 + -8 Combine like terms: 5 + -8 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75
| 7-(-9)= | | 5(4z-1)-5(z+7)=2(z+1) | | -9x+7(2x-7)=-36-8x | | 3ax^2+9b=3 | | 7(2x-3)=20+5x | | 6(5z-1)-4(z+7)=3(z+1) | | 62.00=0.25x+27 | | 443*11=8 | | Y=-3(0)+9 | | -3(2n+1)=6 | | y=0.25(100)+27 | | 15x-4=7x | | _9X+7(2x_7)=_36_8x | | y=0.25(50)+27 | | -9x+7(2x-7)=36-8x | | -2-5x-4=2x+12 | | 11=y-8 | | 3=6x-3x-3x | | 3=6x-3x | | 42-7x=-10 | | 5x+6-6+(2*3)=5x+9 | | -2x=36-20x | | 14-2(x+4)=x+3(4+x) | | 6-2=-14 | | 3(5+2)-8+2(3)= | | 2x^3-5x=3 | | 2x^3-5x+3= | | 2x^3-5x+3=0 | | 2w-4(w+2)=0 | | 107-(-25)= | | 3x+10=2x+5 | | 30=y+(0.07y) |